Gp41 and Gag amino acids linked to HIV‐1 protease inhibitor‐based second‐line failure in HIV‐1 subtype A from Western Kenya. Issue 3 (3rd November 2017) - Coetzer, Mia; Ledingham, Lauren; Diero, Lameck; Kemboi, Emmanuel; Orido, Millicent; Kantor, Rami
Abstract: Introduction: Failure of protease‐inhibitor (PI)‐based second‐line antiretroviral therapy (ART) with medication adherence but no protease drug resistance mutations (DRMs) is not well understood. This study investigated the involvement of gp41 and gag as alternative mechanisms, not captured by conventional resistance testing and particularly relevant in resource‐limited settings where third‐line ART is limited. Methods: We evaluated gp41 and g ag for unique amino acids in seven subtype A infected Kenyans failing second‐line therapy with no PI resistance yet detectable lopinavir (query dataset), compared to seven similar‐setting patients with PI resistance or undetectable lopinavir and 69 publically available subtype A Kenyan whole‐genomes sequences. Results: Three gp41 (607T, 641L, 721I) and four gag (124S, 143V, 339P, 357S) amino acids were significantly more frequent in the query dataset compared to the other datasets, with significantly high co‐occurrence. Conclusion: The genotypic analysis of a unique group of HIV‐1 subtype A infected patients, identified seven amino acids that could potentially contribute to a multi‐gene mechanism of PI‐based ART failure in the absence of PI DR mutations.